Expression of inducible nitric oxide synthase by stimulated macrophages correlates with their antihistoplasma activity. - Lane, T E (1994)
The antihistoplasma activity of recombinant murine gamma interferon (rMuIFN-gamma)-treated macrophages of the RAW 264.7 cell line depends on the generation of nitric oxide (NO.) from L-arginine. Macrophages of the P388D1 cell line treated with rMuIFN-gamma do not produce NO. or inhibit the intracellular growth of Histoplasma capsulatum. NO. is generated by the inducible enzyme nitric oxide synthase (iNOS) formed by stimulated macrophages. Northern (RNA) blot analysis of RAW 264.7 cells revealed the expression of iNOS mRNA after exposure to rMuIFN-gamma. In contrast, rMuIFN-gamma-treated P388D1 cells did not produce detectable levels of iNOS. These data suggest that the failure of P388D1 cells to generate NO. and to restrict the intracellular growth of H. capsulatum is due to a lack of expression of iNOS following treatment with rMuIFN-gamma.